2022
DOI: 10.24127/ajpm.v11i2.4840
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Creative Thinking Mahasiswa Di Politeknik Menggunakan Blended Learning Dan LMS Moodle

Abstract: Tujuan dari penelitian ini adalah untuk melihat tingkat efektivitas dari penggunaan model blended learning dengan menggunakan platform LMS moodle terhadap Mathematical creative thinking di Politeknik. Subjek penelitian adalah mahasiswa jurusan teknik mesin, program studi teknik mesin dan manufaktur di Politeknik Manufaktur Negeri Bangka Belitung yang dipilih secara random. Pemilihan sampel kelas eksperimen dan kelas kontrol menggunakan teknik random sampling. Penelitian ini merupakan penelitian kuantitatif den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Various studies on Blended learning have shown its advantages. Research that has been conducted by (Jemakmun, 2022;Kusuma et al, 2023;Nugraha et al, 2019;Pratiwi & Sari, 2022;Sukma & Priatna, 2021;Yanto & Retnawati, 2018) states that the blended learning model has the ability to improve student freedom, learning outcomes, critical and creative thinking, and mathematical concept understanding. Besides that, according to Sulisworo et al (2020), said that In the case of blended learning, Students who were told to use Schoology as their Learning Management System (LMS) performed better on tests of critical thinking than those who utilized Google Classroom.…”
mentioning
confidence: 99%
“…Various studies on Blended learning have shown its advantages. Research that has been conducted by (Jemakmun, 2022;Kusuma et al, 2023;Nugraha et al, 2019;Pratiwi & Sari, 2022;Sukma & Priatna, 2021;Yanto & Retnawati, 2018) states that the blended learning model has the ability to improve student freedom, learning outcomes, critical and creative thinking, and mathematical concept understanding. Besides that, according to Sulisworo et al (2020), said that In the case of blended learning, Students who were told to use Schoology as their Learning Management System (LMS) performed better on tests of critical thinking than those who utilized Google Classroom.…”
mentioning
confidence: 99%